2016
DOI: 10.1002/smll.201600737
|View full text |Cite
|
Sign up to set email alerts
|

On‐Chip Production of Size‐Controllable Liquid Metal Microdroplets Using Acoustic Waves

Abstract: Micro- to nanosized droplets of liquid metals, such as eutectic gallium indium (EGaIn) and Galinstan, have been used for developing a variety of applications in flexible electronics, sensors, catalysts, and drug delivery systems. Currently used methods for producing micro- to nanosized droplets of such liquid metals possess one or several drawbacks, including the lack in ability to control the size of the produced droplets, mass produce droplets, produce smaller droplet sizes, and miniaturize the system. Here,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
68
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(69 citation statements)
references
References 31 publications
1
68
0
Order By: Relevance
“…In this range, we found that the 30 min sonication results in the highest conductivity of all slurries containing EGaIn droplets and chloroform‐HCl (Figure g). The conductivities of the mixtures depend on both the size and conductivity of the fillers . While the increase of sonication duration generally leads to a decrease in the particle size, it also increases the exposure time of the droplets to the inevitably dissolved oxygen even under N 2 gas protection, resulting in the formation of thicker surface oxide interfacial layers and therefore lower conductivity .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this range, we found that the 30 min sonication results in the highest conductivity of all slurries containing EGaIn droplets and chloroform‐HCl (Figure g). The conductivities of the mixtures depend on both the size and conductivity of the fillers . While the increase of sonication duration generally leads to a decrease in the particle size, it also increases the exposure time of the droplets to the inevitably dissolved oxygen even under N 2 gas protection, resulting in the formation of thicker surface oxide interfacial layers and therefore lower conductivity .…”
Section: Resultsmentioning
confidence: 99%
“…The conductivities of the mixtures depend on both the size and conductivity of the fillers . While the increase of sonication duration generally leads to a decrease in the particle size, it also increases the exposure time of the droplets to the inevitably dissolved oxygen even under N 2 gas protection, resulting in the formation of thicker surface oxide interfacial layers and therefore lower conductivity . This explains why the samples sonicated for optimum duration of 30 min, with the intermediate mean size distribution of 0.97 µm, show the highest conductivity .…”
Section: Resultsmentioning
confidence: 99%
“…As a result, these LMEE composites can be engineered to have a unique combination of elastic, electrical, and thermal properties ( Figure ). More generally, LM droplets can be created through a variety of techniques, including molding ( Figure A), use of acoustic waves (Figure B), microfluidic flow‐focusing (Figure C), shear‐mixing (Figure D,E), and sonication (Figure F,G). As shown in Figure , the LM particle size can range from mm scale (Figure A) to tens and hundreds of nm (Figure H).…”
Section: Lm Dispersionsmentioning
confidence: 99%
“…Acoustics provide a noninvasive and robust transduction mechanism that has been widely used in micromixing, micropumping, particle or cell separation, and manipulation, protein crystal patterning, microfluidic switches, droplet production, drug delivery, and actuation of micro‐ and nanoswimmers . Acoustic wave–induced microvortices around solid structures and bubbles have been used to perform manipulation of small objects .…”
Section: Introductionmentioning
confidence: 99%